Extractant structures and their performance for palladium extraction and separation from chloride media: A review. (15th March 2021) - Wang, Junlian; Xu, Wen; Liu, Hui; Yu, Fengshan; Wang, Huajun
Highlights: 183 compounds were collected and classified into seven major groups. Their Pd extraction mechanism and structure-activity relationships were summarized. Their Pd extraction behaviors, selectivity and stripping etc were commented. Abstract: The continuous extraction and separation of Platinum Group Metals (PGMs) to obtain high purity single PGM product has always been a challenging task. The difficulty is the palladium/platinum separation. This review collected 183 compounds, classified them into seven major groups – sulfides, sulfoxides, thiourea derivatives, neutral organic phosphorus extractants, acidic organic phosphorus extractants, oximes and amine based extractants which include amines, amides and thioamides – according to their functional groups and structural features, summarized and commented these extractants from the aspects of Pd extraction mechanism, extractability, structure-activity relationships, extraction kinetics, acidity effect on Pd extraction efficiency, selectivity and stripping etc.